Expression of CRISP proteins in the male equine genital tract. - Schambony, Alexandra; et al. (Journal of reproduction and fertility. Supplement, 1998)
Cysteine rich secretory proteins (CRISPs) have been detected immunochemically in the equine male genital tract. CRISPs are secretory products of the epididymis, the ampulla and the seminal vesicle. A particular feature of the horse is the abundance of CRISPs in seminal plasma. CRISPs can also be detected in extracts of testicular, epididymal and ejaculated spermatozoa in increasing amounts. Unlike other seminal plasma proteins, they cannot be removed completely from spermatozoa by high salt treatment. The remaining CRISP antigens are localized on the midpiece, and the postacrosomal and equatorial region of the sperm head. Tissue distribution and localization of CRISPs on equine spermatozoa point to a role of these proteins in epididymal sperm maturation and equine reproduction.
Keywords: get pdf